Correlation and Path Coefficient Analysis of Yield and Quality Components of Some Sunflower (Helianthus annuus L.) Cultivars. - OZTURK, O.; ADA., R. (Asian Journal of Chemistry, 2010)
The purpose of this research was to determine the simple correlations between yield and yield components and direct and indirect effects of these characters on seed yield and oil yield in sunflower. Plant height, head diameter, 1000 seed weight, hull ratio, seed yield, oil content and oil yield were determined for 15 sunflower (Helianthus annuus L.) cultivars. Statistically significant variations were found by ANOVA amongst the cultivars for all the variables examined (p < 0.01). The oil yield of sunflower varieties varied between 1008.1 and 1842.8 kg ha-1. Correlations amongst the variables as well as their direct and indirect effects on oil yield, oil content and seed yield were also calculated using the correlation and path coefficients analyses, respectively. In the examined characteristics, positive and statistically significant relationships were found between seed yield and 1000 seed weight (r = 0.416**), oil content (r = 0.252*) and oil yield (r = 0.907**); between oil yield and 1000 seed weight (r = 0.291**), oil content (r = 0.632**). Negative and statistically significant relationships were determined between seed yield and plant height (r= -0.266*); between plant height and head diameter (r = -0.257*); between oil content and head diameter (r = -0.570**), hull ratio (r = -0.472**); between oil yield and head diameter (r = -0.220*). Path coefficient analyses indicated that 1000 seed weight (2.86 %), seed yield (88.06 %) and oil content (64.34 %) had a positive direct effect whereas head diameter (9.62 %) had a negative direct effect on oil yield. Other traits (plant height and hull ratio) showed no significant effects for oil yield and their effect to oil yield was covered by indirect effect of seed yield and oil content.